A Further Enhancement of Least Significant BIT Algorithm applied in image Steganography - Chavez, Stephannie Carl G. and Jacinto, Joana Clariz S. 4 0 16; 5
u
Undergraduate Thesis: (BSCS major in Computer Studies) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2